A systematic review on the profiling of digital news portal for big data veracity - Che Eembi @ Jamil, Normala; Ishak, Iskandar; Sidi, Fatimah; Affendey, Lilly Suriani; Mamat, Ali (Elsevier, 2015)
Currently, digital news portals have been one of the most important news sources for Internet users. However, the way it is written depends on the direction of the content. One approach to news reporting is through manipulative writing. Such method of writing has created a number of adverse outcomes such as political unrest, slander and negative perception towards the particular organization, personnel, and country. It is important for readers to choose and select news portal that is reporting positively and to neglect portals which practices manipulative writing approach for their own gains or causing negative impact towards the community. The aim of this study is to structure and analyzed the literature related to data veracity research that can be used to the profile of digital news portal. The method that has been used in this paper is to classify and define data veracity; a systematic literature review is a conduct. It includes journal and conference proceedings. The results come out with objectives in data veracity, the structure of research topics, research trends with publications and framework veracity model validated. This paper provides a complete review of literature related to profiling digital news portal in data veracity.